The Role of Physical Activity in Preventing and Treating Erectile Dysfunction: Review - Michalak, Katarzyna; Jarych, Weronika; Zukierski, Krystian; Mazur, Michał; Żak, Katarzyna; Jucha, Hubert; Madyniak, Katarzyna; Pliszka, Aleksandra; Kluz, Agnieszka (Quality in Sport, 2025)
Introduction and aim: Erectile dysfunction has a significant impact on quality of life, substantially reducing both the mental and physical well-being of the affected men. This study examines the role of physical activity in the prevention and treatment of erectile dysfunction. Methods and materials: A comprehensive literature review was undertaken using the PubMed and Google Scholar databases, focusing on studies published between 2010-2025. The search strategy aimed to gather anextensive range of research on the role of physical activity on the course of ED. Key search terms included “impotence”, “erectile dysfunction”, “physical activity”, “exercise”. Results and conclusion: Regular physical activity plays a key role in preventing and treating erectile dysfunction by improving cardiovascular health, managing obesity and diabetes, regulating testosterone, and enhancing overall well-being. The review highlights aerobic exercise as the most effective, with added benefits from strength training and pelvic floor exercises. Even low-intensity activity like walking can help. Long-term, consistent training is essential, and exercise plans should be tailored to individual needs and abilities. For best results, physical activity should be part of a broader lifestyle change.